Determinan Sensitivitas Lingkungan: Peran ESG dan Sumber Daya Keuangan Perusahaan Agroindustri Indonesia - Aprillianto, Bayu; Adhani, Brillian Farel; Maulidy, Rafly Syah (Fakultas Ekonomi dan Bisnis Universitas Panca Marga, 2025)
The increasing pressure on agro-industrial companies to contribute to climate change mitigation and environmental pollution, particularly in Indonesia, is linked to issues of deforestation. This study aims to empirically examine the effect of Environmental, Social, and Governance (ESG) performance, company size, capital structure, and profitability on environmental sensitivity in agro-industrial companies listed on the Indonesia Stock Exchange during the period of 2019–2021. The research method employed is multiple linear regression with a quantitative approach. The results of the study indicate that, simultaneously, all four independent variables significantly affect environmental sensitivity. In particular, ESG performance and company size have a positive and significant effect on environmental sensitivity, while capital structure and profitability do not show a significant influence. These findings highlight the importance of strengthening sustainability commitments and business scale to enhance corporate environmental responsibility. This research is expected to serve as a reference for regulators and stakeholders in designing more effective environmental management policies and strategies in the agro-industrial sector. Keywords: Capital Structure, Environmental Sensitivity, ESG, Firm Size, Profitability